Cost of living, salaries, consumption and the situation of the Italian middle classes - G. TAGLIACARNE (PSL Quarterly Review, 2014)
The article examines and compares the recent developments arising from the depreciation of the lira. The author calls attention to some disturbances of social importance caused by recent inflationary phenomena in Italy; more especially to the erosion of real wages and the tendency to level down remuneration, a tendency leading to serious disruptions in the status of some of the most valuable categories of the Italian middle class.